Implementation of Management Based School in Improving The Quality Of Secondary Education - Istijarti, Atiek; Riyanto, Yatim; Setyowati, Sri (Universitas Malikussaleh, 2019)
The implementation of school-based management in Indonesia itself is contained in the Act National Education System Number 20 of 2003 which reads